Prospects of carbon fiber composites applications in hydraulic supports - Guo, Haiwei; Zhou, Miaomiao; Li, Pengfei; Lv, Meng; Zhang, Yufang (Frontiers in Materials, 2022)
This paper briefly analyzes the current development of lightweight design and applications for hydraulic support in the coal mines. Specifically, the comparative investigations of lightweight design demonstrate the potential application for carbon fiber reinforced composites (CFRP) in the production and manufacturing process of hydraulic support. With analyzing three detailed industrial utilizations of CFRP, hydraulic structure, cylinder and special frames, it is predicted the feasibility of the potential applications of CFRP in the future research of hydraulic support in coal mining sites.